Biotechnology as priority direction industrial and innovative development of Kazakhstan - Каренов, Р.С. (Fundamental and Experimental Biology, 2015)
It is noted that biotechnologies as «global technologies», cover a wide range of scientific disciplines, sectors of economy and extend on enormous territories of our planet. Locates that in XXI century they can cause a powerful wave of production of innovative products and services in medicine, agriculture, the industry, the electronic engineer, the power engineering specialist, thatis practically in overwhelming quantity of sectors of economy of the Republic of Kazakhstan. Is shown that application of innovative biotechnologies will give the chance in XXI century to provide with the food increasing population of Earth, and also drinking water and other natural resources on the basis of increase of efficiency of use of capacities of the biosphere, the hydrosphere, the atmosphere and a lithosphere. The conclusion is drawn that development in the long term of bio-energetics will demand wide use of biotechnologies for biomass cultivation. Modern types of biofuel which include are described: the ethanol extracted from cellulose, sugar and starch (except for grain starch), waste of processing of grain crops and vegetables, animal and food waste; diesel fuel from biomass; the biogas made on the basis of biomass conversion, and other types of the biofuel extracted from cellulose biomass. The attention to application of biotechnologies for environment protection at the enterprises of mining sector of economy is paid.